Pengaruh Motivasi, Pendidikan Kewirausahaan, Ekspektasi Pendapatan, Efikasi Diri, dan Digital Marketing Terhadap Minat Berwirausaha Mahasiswa di Masa Pandemi Covid-19 - Urbaningtyas, Laela Novita; Purwati, Atiek Sri; Sugiarto, Sugiarto; Pratiwi, Umi (Soedirman Accounting, Auditing and Public Sector Journal, 2022)
This study aims to determine the effect of Motivation, Entrepreneurship Education, Income Expectations, Self-Efficacy, and Digital Marketing on Student Entrepreneurial Interest in the Covid-19 Pandemic Period. The population in this study were undergraduate students of Accounting, Faculty of Economics and Business, Jenderal Sudirman University Class of 2018 and 2019. The sample in this study was 75 accounting students, consisting of 38 students from the 2018 class and 37 students from the 2019 class. The data collection technique in this study was a questionnaire. Data were analyzed using multiple linear regression analysis. The results of this study indicate that: (1) Motivation has a positive effect on student interest in entrepreneurship; (2) Entrepreneurship Education has a positive effect on student interest in entrepreneurship; (3) Income Expectations have no effect on students' interest in entrepreneurship; (4) Self- fixation has a positive effect on student interest in entrepreneurship; (5) Digital Marketing has a positive effect on students interest in entrepreneurship.